The Utilization of the European Standards for Defining Educational Assessment: Teacher-Tester Attributes and Directors’ Control - Nurdan Kavaklı; İsmail Hakkı Mirici (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
This study aims to scrutinize the utilization of the European guidelines in testing and assessment practices of non-formal English language schools. Providing insights from a mixed-methods research design, the quantitative data were gathered from the English language teachers, who were also working as test (-item) developers at three private institutions renowned for quality with the highest course attendee capacity and branches in Turkey to reveal teacher-tester attributes, whereas qualitative data were gathered from the directors of these private institutions to screen directors’ control. The results have yielded that (1) the kinds of assessment in use allow for feedback on the performance of the on-going educational system; (2) the overall evaluation of the total program, and assessment of educational systems are taken into consideration in testing procedures to some extent; (3) what is good for the individual in assessment does not thoroughly align with the United Nations Convention on the Rights of the Child; (4) the assessment applied in the selected private institutions does not mainly cover standardized tests. The results are discussed, and laced with suggestions to improve the quality of current testing and assessment practices by the exploitation of the European Framework of Standards for Educational Assessment (AEA- Europe 2012) regarding non-formal private institutions as the arteries of Turkish education economy.